Mosaic Xq duplication, or 46,X,der(X)dup(X)(q22.1q22.2)dup(X)(q25q22.3)/ 46,XX at amniocentesis in a pregnancy with a favorable outcome - Chih-Ping Chen; Tsang-Ming Ko; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Meng-Shan Lee; Wayseen Wang (Elsevier, 2021)
Objective: We present mosaic Xq duplication, or 46,X,der(X)dup(X)(q22.1q22.2)dup(X)(q25q22.3)/46,XX at amniocentesis in a pregnancy with a favorable outcome. Case Report: A 40-year-old woman underwent amniocentesis at 16 weeks of gestation because of advanced maternal age. Amniocentesis revealed a result of 46,X,der(X)dup(X)(q22.1q22.2)dup(X)(q25q22.3)[7]/46,XX[20]. Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (1-22, X) × 2. Cytogenetic analysis on maternal blood revealed a karyotype of 46,XX. At 22 weeks of gestation, she underwent repeat amniocentesis which revealed a karyotype of 46,XX in 22/22 colonies of cultured amniocytes and an aCGH result of (1-22, X) × 2 in the uncultured amniocytes. Prenatal ultrasound findings were unremarkable. The parents decided to continue the pregnancy, and a healthy female baby was delivered at 39 weeks of gestation with a body weight of 3510 g and a body length of 49 cm. The cord blood had a karyotype of 46,X,der(X)dup(X)(q22.1q22.2)dup(X)(q25q22.3)[3]/46,XX[37]. At age two months, interphase fluorescence in situ hybridization (FISH) analysis on buccal mucosal cells showed Xq duplication signals in 1.25% (1/80 cells), compared with 0% (0/90 cells) in the normal control. At age nine months, the neonate had normal physical and psychomotor development. Her body weight was 9.6 Kg (85th - 97th centile), and body length was 72 cm (50th - 85th centile). Cytogenetic analysis of peripheral blood revealed a karyotype of 46,X,der(X)dup(X) (q22.1q22.2)dup(X)(q25q22.3)[1]/46,XX[39]. Interphase FISH analysis on 100 buccal mucosal cells revealed no abnormal signal. Conclusion: In case of mosaicism for an Xq duplication with a normal euploid cell line at amniocentesis, the in-vitro culture process of amniocytes may cause over-estimation of the mosaic level for the aberrant chromosome because of culture artifacts, and the abnormal cell line can decline after birth.